2021
DOI: 10.1108/jbim-02-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

Placebo outsourcing: when does provider’s bluffing enhance customer satisfaction?

Abstract: Purpose Drawing on signaling theory, this paper aims to argue in favor of a “placebo outsourcing effect” (POE) consisting of a positive relationship between provider’s bluffing and customer satisfaction. Design/methodology/approach The authors applied prediction-oriented segmentation SEM on a dyadic sample of 171 outsourcing relationships. Findings The authors highlighted two segments that display a form of POE, representing about three-quarters of the customer-provider dyads. The first segment exhibits a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The use of management tools is widely established in business management (Rigby and Bilodeau, 2005) and FM services (Amos et al, 2019). In service-sourcing contexts, the ongoing evolution and improvement of management tools are necessary for cost control and minimization of value leakage in service delivery processes (Ellram et al, 2004), efficient evaluation processes and desired service outcomes (Florea et al, 2022;Haensel and Hofmann, 2018). An essential aspect of service sourcing is the formulation and specification of service-level agreements (SLAs) (Beaumont, 2006) that are often characterized by ongoing modifications throughout the contract period (Molin and Åge, 2017).…”
Section: Management Tool Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of management tools is widely established in business management (Rigby and Bilodeau, 2005) and FM services (Amos et al, 2019). In service-sourcing contexts, the ongoing evolution and improvement of management tools are necessary for cost control and minimization of value leakage in service delivery processes (Ellram et al, 2004), efficient evaluation processes and desired service outcomes (Florea et al, 2022;Haensel and Hofmann, 2018). An essential aspect of service sourcing is the formulation and specification of service-level agreements (SLAs) (Beaumont, 2006) that are often characterized by ongoing modifications throughout the contract period (Molin and Åge, 2017).…”
Section: Management Tool Developmentmentioning
confidence: 99%
“…In service-sourcing contexts, the ongoing evolution and improvement of management tools are necessary for cost control and minimization of value leakage in service delivery processes (Ellram et al. , 2004), efficient evaluation processes and desired service outcomes (Florea et al. , 2022; Haensel and Hofmann, 2018).…”
Section: Literature Review – Business Streamliningmentioning
confidence: 99%
“…Despite accepted theory, deception can harm satisfaction (Eckerd and Hill, 2012) and trust (Hill et al , 2009). Skillful bluffing raises buyer satisfaction, but buyers can mitigate its effects (Florea et al , 2022). Rottenburger and Kaufmann (2020) found that when a supplier was perceived as new, it was also perceived as more deceptive.…”
Section: Literature Reviewmentioning
confidence: 99%